2022
DOI: 10.15678/eber.2022.100110
|View full text |Cite
|
Sign up to set email alerts
|

The role of mindfulness and perceived social support in promoting students’ social entrepreneurial intention

Abstract: This study aims to demonstrate the positive relationships between mindfulness, perceived social support, and social entrepreneurship intention (SEI) using the theory of planned behaviour (TPB). Research Design & Methods:This study surveyed 525 students who have been taking social entrepreneurship courses of non-profit organizations in Vietnam. Data was collected through a pre-designed questionnaire at Google Form from August to October 2020 and analysed by structural equation modelling to verify the research m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 83 publications
4
9
0
Order By: Relevance
“…SS influences ESE directly and significantly (H2). The findings support the hypothesis proposed in earlier studies ( Khayru et al, 2021 ; Bui Ngoc Tuan and Pham, 2022 ). Bui Ngoc Tuan and Pham (2022) found that ESE is proportional to the amount of SS an individual receives from the surrounding environment.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…SS influences ESE directly and significantly (H2). The findings support the hypothesis proposed in earlier studies ( Khayru et al, 2021 ; Bui Ngoc Tuan and Pham, 2022 ). Bui Ngoc Tuan and Pham (2022) found that ESE is proportional to the amount of SS an individual receives from the surrounding environment.…”
Section: Discussionsupporting
confidence: 93%
“…The findings support the hypothesis proposed in earlier studies ( Khayru et al, 2021 ; Bui Ngoc Tuan and Pham, 2022 ). Bui Ngoc Tuan and Pham (2022) found that ESE is proportional to the amount of SS an individual receives from the surrounding environment. The more support an individual receives, the higher their level of self-efficacy will be.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations